Segmented or Competitive Labor Markets - Magnac, Th. (Econometrica, 1991)
A normal Roy model with four sectors is developed. It allows to derive tests of several assumptions on the working of the labor market: strongly or weakly competitive or segmented. It shows that more important a feature of labor markets than segmentation is the presence of comparative advantages for individuals between the various economic sectors. The model is applied to data on women's labor-force participation in the main towns of Colombia in 1980. It uses multivariate probit and Tobit techniques. Copyright 1991 by The Econometric Society.